High-performance double-network ionogels enabled by electrostatic interaction. Issue 13 (2nd March 2020) - Zhang, Yawen; Chang, Li; Sun, Peiru; Cao, Ziquan; Chen, Yong; Liu, Hongliang
Abstract : A universal strategy to produce high-performance ionogels has been developed by considering electrostatic interactions between polymer double networks and IL. Abstract : Production of highly conductive and mechanically robust ionogels is urgently needed for the development of diverse flexible electrical devices, but it remains challenging. Herein, we report a facile strategy to prepare high-performance ionogels (ionic conductivity of 1.9 S m −1, fracture strain of 170%) via electrostatic interaction between mechanically robust charged gel double networks and conductive ionic liquids. Ionogels based on charged polymer networks (with electrostatic interaction) exhibit obvious higher optical transmittance, ionic conductivity, and better mechanical properties compared with those based on neutral polymer networks (without electrostatic interaction). Ionic conductivity and mechanical properties of the ionogels can also be regulated by the double-network structure of the gels. We further develop an ionic skin sensor with the high-performance ionogels used as ionic conductors, which can exhibit excellent sensing performance even under harsh conditions. We envision that this new class of high-performance ionogels would be an attractive alternative to traditional hydrogels, and would extend the applications of ionic conductors to extreme environments.